Anchor lipoabdominoplasty - Francisco Mendonça de Albuquerque; Patrícia Pimentel Pizarro; Osvaldo Ribeiro Saldanha; Sérgio Mitiake Shimizu; Irineu Rasera (Revista Brasileira de Cirurgia Plástica)
Morbid obesity is characterized by the accumulation of adipose tissues distributed heterogeneously throughout the body, and gastroplasty is the latest method of surgical treatment. After considerable weight loss, patients present with excess skin under which secretions accumulate, increasing susceptibility for skin infections, which can be minimized with dermolipectomy. Herein, we describe the anchor lipoabdominoplasty technique, adapting the principles of reduced flap detachment, abdominal and flank liposuctions, and preservation of the infraumbilical Scarpa's fascia associated with the preoperative fleurde- lis marking. The technique was used for seventeen patients, including sixteen women and one man, with late postoperative gastroplasty, aged 35-66 years in the period from January 2018 to June 2019. The patients presented with normal preoperative testing, satisfactory clinical conditions, and body mass index scores less than 30 kg/m2. In the present case series, one patient had umbilical cord remnant epidermolysis; all patients had edema and ecchymosis; and one patient had seroma on postoperative day 13. Hematoma, necrosis, infection, wound dehiscence, or thromboembolic events were not observed in any patient. The technique is safe and effective in the treatment of patients with abdominal excess skin, improving their body contour. However, longer postoperative follow-up periods and more cases are necessary to better measure the results and incidence of complications.